Analisis Rasio Keuangan Terhadap Kinerja Keuangan Pada PT. Garudafood Putra Putri Jaya Tbk (GOOD) yang Terdaftar di Bursa Efek Indonesia Periode 2019 - 2024 - Anggi, Anggi; Firayanti, Yuni; Mahardhika, Tubagus (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
This study aims to analyze the financial performance of PT. Garudafood Putra Putri Jaya Tbk (GOOD) listed on the Indonesia Stock Exchange for the 2019 - 2024 period through a financial ratio analysis approach. The research method used is Qualitative Descriptive with secondary data in the form of the company's annual financial reports. The analysis was carried out using liquidity ratios (Current Ratio and Quick Ratio), solvency ratios (Debt to Asset Ratio and Debt to Equity Ratio), profitability ratios (Return on Asset, Return on Equity, and Net Profit Margin), and market ratios (Earnings Per Share). The results of the study indicate that the financial performance of PT. Garudafood fluctuated during the 2019 - 2024 period where the Current Ratio and Quick Ratio liquidity ratios were below industry standards, indicating the company's ability to meet short-term obligations still needs to be improved. The Debt to Asset Ratio solvency ratio exceeds industry standards, indicating the company's high dependence on debt funding. The Debt to Equity Ratio exceeds industry standards, indicating an increasing dependence on debt. Profitability ratios (ROA, ROE, and NPM) have consistently been below standard, reflecting challenges in generating optimal profits. Meanwhile, Earnings Per Share (EPS) has increased significantly, indicating improved market performance.